Reliability and accuracy of quantitative sensory testing for oxaliplatin‐induced neurotoxicity. (14th October 2014) - Velasco, R.; Videla, S.; Villoria, J.; Ortiz, E.; Navarro, X.; Bruna, J.
<x xml:space="preserve">Abstract</x> Objectives Thermal quantitative sensory testing (QST) is a non‐invasive procedure helpful in the assessment of the function of small Aδ and C nerve sensory fibres. Oxaliplatin (OXA) is an effective chemotherapeutic agent, but is frequently associated with neurotoxic dose‐limiting side effects. This controlled clinical trial evaluated the reliability and accuracy of thermal QST for assessing the OXA‐induced acute neuropathic syndrome, whose clinical hallmark is cold‐triggered painful paraesthesia. Materials & methods A testing protocol with the Thermal Sensory Analyzer (Medoc) was carried out in 20 colorectal cancer patients during the initial four cycles of OXA‐based chemotherapy and in 20 age‐ and sex‐matched healthy volunteers. Testing was carried out on the hands and included the determination of thermal detection and pain thresholds and the intensity of pain evoked by cold stimuli. Calculations were made of: coefficients of test–retest and inter‐rater reliability, indices of responsiveness and parameters that quantify diagnostic accuracy. Results Thermal thresholds showed moderate to good reliability (ρ ≥ 0.383), but were not consistently responsive to the effects of chemotherapy (cold pain thresholds decreased in both groups, although almost twice in patients compared to healthy volunteers). Conversely, the intensity of pain evoked by suprathreshold cold stimuli was reliable (ρ ≥ 0.822), responsive (detected changes over time) and discriminated between patients and healthy volunteers (area under the ROC curve = 0.700). Conclusions The procedure was reliable and accurate to evaluate cold hyperalgesia resulting from OXA administration. The data provided may be used to define efficacy endpoints for future clinical trials of therapies for OXA‐induced neuropathies and calculate appropriate sample sizes.